(untitled) (Dristikon: A Multidisciplinary Journal, 2023)
Human capital is widely recognized as the fundamental basis for a nation’s ability to maintain a high standard of living. This paper aims to evaluate Nepal’s human capital and its impact on poverty reduction. The study utilizes time series data spanning from 1990 to 2021. To achieve the objectives of this research, the Johansen cointegration, vector error correction model (VECM), and Granger causality methods are employed. The overall findings reveal that human capital formation is particularly effective and significant in reducing poverty in Nepal in the short term. There is strong evidence indicating that investing in health is crucial for sustainable poverty reduction. However, education spending appears to have only a temporary effect on poverty alleviation in Nepal. Additionally, education demonstrates a positive association with gross fixed capital formation, employment, gross enrollment, and HDI, but not with health spending. It’s important to note that this study covers a limited observation period of 32 years, and proxies for variables such as poverty reduction and human capital are constrained. Nevertheless, this research contributes by employing updated time-series data and aims to address the literature gap regarding the relationship between human capital and poverty reduction in Nepal. To effectively combat poverty in Nepal, the government should need to finance healthcare and education. Simultaneously, a policy emphasizing investment in both education and healthcare should be implemented, as this will contribute to fixed capital formation and enhance the quality of life through employment and income generation.